Desecuritizing the 'war on drugs' (2017)
This chapter makes use of Colombian-US bilateral relations as a window to trace the evolution of the US-designed ‘war on drugs’, highlighting the role of securitization in the development of counternarcotics activities in Colombia and discussing the process through which the shortcomings of this policy have created opportunities to engage in desecuritization and to design alternative strategies. It explores the principles that have sustained the ‘war on drugs’ and the evolution of Colombian-US relations since 1998, providing an overall assessment of the anti-drug strategy that helps to analyse the possibilities of desecuritization in the light of the Copenhagen school’s securitization theory. Finally, the chapter identifies the challenges that drug policy reform currently faces in Colombia and Latin America more generally.